The Effect of Outpatient Interventional Audiology on Inpatient Audiology Services - Zitelli, Lori; Palmer, Catherine V. (Seminars in Hearing, 2017)
Although older adults are likely to experience some degree of hearing loss that if untreated will interfere with treatment for other disorders and result in less-than-optimal health care outcomes, health care providers do not have a reliable and cost-effective way to identify these individuals when admitted to a hospital for inpatient care. This article addresses the impact of untreated hearing loss on health care in a hospital setting and shares how the implementation of interventional audiology in an outpatient clinic has impacted the inpatient audiology services provided at a large tertiary care hospital. A discussion of how these services can be further expanded is provided.
Keywords: Interventional audiology; inpatient audiology services; hearing loss; healthcare